Optimization of working parameters for 3MGY-200 axial air-assisted sprayer in kiwifruit orchards - Gu, Chenchen; Liu, Zhijie; Pan, Guanting; Pu, Yingjun; Yang, Fuzeng (International Journal of Agricultural and Biological Engineering, 2020)
Axial air-assisted sprayers can distribute pesticides efficiently in kiwifruit orchards. Because of improper parameter settings, most sprayers deliver either too much or too little pesticide. To identify appropriate sprayer parameters for kiwifruit trees, the vertical distribution profiles of the applied liquid spray were examined in this study. The effects of spray fan speed (SFS), spray pressure (SP) and spray distance (SD) on the distributions of the sprayed liquid in the vertical profiles were studied. Combined actions of the above parameters were systematically analysed using the quadratic general rotary design test method. Regression equations for the spray liquid distributions and working factors are presented. Field confirmation experiments were carried out to optimize the parameters. Data analysis showed that the optional sprayer working parameters are those of Group 3, with an SFS equal to 1900 r/min and SP equal to 3.25 MPa. The results of this study provide a reference for future applications of this type of axial air-assisted sprayer in kiwifruit orchards. Keywords: sprayer parameters, quadratic general rotary unitized design, regression equation, optimization, kiwifruit tree DOI: 10.25165/j.ijabe.20201302. Citation: Gu C C, Liu Z J, Pan G T, Pu Y J, Yang F Z. Optimization of working parameters for 3MGY-200 axial air-assisted sprayer in kiwifruit orchards. Int J Agric & Biol Eng, 2020; 13(2): 81–91.